"Putting Food back on the table": Decolonising towards a Sustainable University that Feeds Us in South Africa. Issue 2 (3rd July 2018) - Magoqwana, Babalwa
Abstract: The higher education landscape in South African (SA) has recently experienced a wave of student movement organised under the #MustFall campaign, where students demanded quality and accessible higher education. This movement spoke against the colonial character of the curriculum, demographic representation, institutional cultures, and architecture of the university in South Africa today, which excludes the majority of the students who cannot access higher education in South Africa. It is in this context that the high cost of higher education was questioned, with some questioning the very "idea of the university", and the role of the university in a society contending with income inequalities, unemployment, and poverty. This article seeks to position food at the centre of decolonising tools towards a sustainable African university of the future. Looking at growing levels of hunger, and the lack of access to food among our students, I argue that in putting food at the centre, regarding our understanding of the curriculum, shape, size, and future of the university in South Africa, we might begin to transform the exclusivist, uncaring and elitist spaces that define a university. In trying to rethink the ''idea of the university'' in South Africa I look at one of the enduring institutions of knowledge in African societies— uMakhulu ("Senior Mother/Grandmother") as a body that can reconnect the African university to its matriarchal heritage, in order to define a university that can feed itself beyond the narrow neoliberal understanding of sustainability.